2009
DOI: 10.1145/1595496.1562891
|View full text |Cite
|
Sign up to set email alerts
|

Freedom of choice as motivational factor for active learning

Abstract: Freedom to choose what, when, and how to contribute in a learning process can motivate students to actively engage and achieve more in their studies. However, freedom of choice complicates course management and may deter instructors from allowing such freedom. Our approach is to utilize existing functionality of course management systems such as Moodle to automatically facilitate and coordinate free student choices and provide much needed relief for instructors at the same time. Using Moodle we have developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(19 reference statements)
0
2
0
1
Order By: Relevance
“…The learning can be enhanced and learner apathy reduced when the students have control over their learning. This could majorly aid student engagement (Radenski, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The learning can be enhanced and learner apathy reduced when the students have control over their learning. This could majorly aid student engagement (Radenski, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Students need enough freedom to become cognitively active in the process of sense making . Although not specifically about inquiry learning, an empirical study on encouraging online active learning found that offering students with instructor-assisted freedom of choice motivated students to actively engage and achieve more in their online studies (Radenski, 2009). There is strong agreement that when designing a support for inquiry learning, it is important to balance between the amount of guidance provided and the amount of freedom allowed for .…”
Section: Support For Hypothesis Generationmentioning
confidence: 99%
“…En los últimos años, el aprendizaje activo se ha convertido en una de las aproximaciones pedagógicas más importantes de cara a fomentar la motivación y satisfacción de los alumnos (Radenski 2009). Está demostrado que los alumnos ven mermadas sus capacidades para concentrarse en atender durante una clase cuando su papel es meramente pasivo.…”
Section: Introductionunclassified